Capturing the Familiness of Family Businesses: Development of the Family Influence Familiness Scale (FIFS). (September 2017) - Frank, Hermann; Kessler, Alexander; Rusch, Thomas; Suess–Reyes, Julia; Weismeier–Sammer, Daniela
This article develops a familiness scale measuring the family influence on the business via decision premises that express familiness. In three studies, we examine familiness with qualitative and quantitative approaches based on new systems theory. Narrative interviews are employed to generate items. Exploratory and confirmatory factor analyses led to a multidimensional scale (Family Influence Familiness Scale [FIFS]) comprising six dimensions: (1) ownership, management, and control; (2) proficiency level of active family members; (3) sharing of information between active family members; (4) transgenerational orientation; (5) family–employee bond; and (6) family business identity. Results indicate high reliability and validity levels.